2014
DOI: 10.5664/jcsm.3874
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Education Improves the Sleep Duration of Adolescents: A Randomized Controlled Pilot Study

Abstract: A commentary on this article appears in this issue on page 793.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 36 publications
2
64
2
3
Order By: Relevance
“…Although all studies reported delivering at least basic knowledge about sleep physiology and/or sleep hygiene, the scope and aims of the programs fell into one of two groups; those who sought solely to disseminate information and improve sleep knowledge, 21,[23][24][25] and those who sought to actively change sleep behavior. [17][18][19][20]22,[26][27][28] Seven themes that were identified from the studies are listed below in no particular order:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although all studies reported delivering at least basic knowledge about sleep physiology and/or sleep hygiene, the scope and aims of the programs fell into one of two groups; those who sought solely to disseminate information and improve sleep knowledge, 21,[23][24][25] and those who sought to actively change sleep behavior. [17][18][19][20]22,[26][27][28] Seven themes that were identified from the studies are listed below in no particular order:…”
Section: Resultsmentioning
confidence: 99%
“…There are currently only 12 [17][18][19][20][21][22][23][24][25][26][27][28] worldwide published studies of sleep education programs focussed on adolescents (with one in press 30 ) that describe their education programs in suffi cient detail for scrutiny. Many factors may contribute to a successful sleep education program, so it is important to understand what these may be in order to optimize efficacy in future sleep education programs.…”
Section: Lessons Learned From Sleep Education In Schools: a Review Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Similar integration of the ACES program with other core subjects and refinement using different modes of instruction could enhance the program that has already showed potential for sleep knowledge 14 and/or behavior change in adolecents. 3 Despite the aforementioned challenges, the authors have been successful in getting school districts in two countries to integrate the intervention into the respective health education programs. The current articles is casted as a "pilot" study and lessons learned from this small RCT, together with the previous studies on ACES, prepare them for larger implementation.…”
Section: Department Of Disability and Psychoeducational Studies Univmentioning
confidence: 99%
“…1 Data also support that over two-thirds of students do not achieve 9 hours, 2 and almost half of adolescents sleep 8 or less hours on school nights. 3 During adolescence, shorter total sleep time (TST) is associated with higher levels of depressed mood, disruptive behaviors, lower grades, and more absences.…”
Section: O M M E N T a R Ymentioning
confidence: 99%